Attitude to illness in pancreatic diabetes patients - M. M. Petrova; T. A. Rachko (Бюллетень сибирской медицины)
The study of the psychological status of 224 type 1 and 2 pancreatic diabetes (PD) patients has revealed the dominant types of the attitude to illness. In type 1 PD patients, regardless of the sex, the dominant type was ergopatic, which may lead tounsatisfactory results of treatment. However, the anosognosiс type of attitude was observed reliably more often in men with type PD than in women. In type 2 PD patients, the harmonic type dominated. At the same time, the disturbing type was observed in women, but not diagnosed in men with type 2 PD.